"أثر الاستثمار الأجنبي المباشر على الطاقات المتجددة - دراسة حالـــــــــــة الجزائـــــر (2000-2020)- " - إبراهيم خليل, شكيمة; محمد التجاني, كرطي (University of eloued جامعة الوادي, 2021)
"لقد عمدت الجزائر من أجل تنويع مصادرها الطاقوية المهددة بالنفاد إلى تبني مجموعة التدابير من أجل تأمين الطاقة لأجيالها الحالية والمستقبلية، ولأجل كل هذا فرض على الجزائر النظر في إستراتيجياتها الطاقوية من خلال تطوير الطاقات المتجددة، لذلك عمدت إلى تبني مجموعة من المشاريع في هذا المجال مع توفير بنية مؤسسية وتشريعية داعمة لهذا المسار الاستراتيجي الفعال في ظل التطورات الاقتصادية التي عرفتها الساحة الدولية. ولقد واكبت حركة الاستثمار الأجنبي التطورات التاريخية التي عاشتها الجزائر أثناء بناء اقتصادها الاشتراكي من خلال المخططات بعد الاستقلال، والى المنعطف الكبير الذي قامت به بعد أزمة البترول نحو اقتصاد السوق وما صاحبه من إصلاحات هيكلية وصولا إلى معرفة الأوضاع التي آل إليها الاستثمار الأجنبي في ظل الإصلاحات وهو ما سنتناوله في هذا البحث. كما أن الجزائر تمتلك من الامكانات الطاقوية في هذا المجال ما يؤهلها، في بناء اقتصاد متنوع وقوي، إلا أن الاستثمار الأجنبي في هذه الطاقات في الجزائر يلقى العديد من العوائق كارتفاع التكاليف، عدم الجدية في التوجه للاستثمار في هذا القطاع...، فاستهلاك الطاقة التقليدية حاليا يعتبر أفضل لمسار النمو الاقتصادي في المدى القصير إلى المتوسط بالجزائر، كون استثمارات الطاقات المتجددة تستلزم الدعم الحكومي بالإضافة إلى صعوبة إحلال بني وهياكل استغلال الطاقات التقليدية بتكنولوجيات الطاقات المتجددة حاليا نظرا للتكاليف الباهضة والتكنولوجيا الفتية في السوق، بالإضافة إلى خصائص المزيج الطاقوي للجزائر والتي تعتمد على الوقود الأحفوري والذي من غير الممكن إحلاله حاليا بتطبيقات الطاقات المتجددة دون تدخل من طرف القطاع الحكومي في شكل إنفاق على البحث والتطوير وتشجيع استغلال تطبيقات الطاقات المتجددة محليا، وهو ما أدى إلى الأثر السلبي على معدلات النمو. وقد خلصت دراستنا إلى أهم النتائج التالية: - أن الاستثمار الاجنبي المباشر لا يسبب استخدام الطاقات المتجددة عند مستوى معنوية 5%. - أن استخدام الطاقات المتجددة لا يسبب الاستثمار الاجنبي المباشر عند مستوى معنوية 5%. - أن التلوث البيئي لا يسبب استخدام الطاقات المتجددة عند مستوى معنوية 5 %. - أن استخدام الطاقات المتجددة لا يسبب التلوث البيئي عند مستوى معنوية 5 %. - أن التلوث البيئي لا يسبب الاستثمار الاجنبي المباشر عند مستوى معنوية 5 %. - أن الاستثمار الاجنبي المباشر يسبب التلوث البيئي عند مستوى معنوية 5 %. ""In order to diversify its energy sources that are threatened with depletion, Algeria has adopted a set of measures in order to secure energy for its current and future generations. For all this, Algeria has to consider its energy strategies through the development of renewable energies. Therefore, it has adopted a number of projects in this field while providing An institutional and legislative structure that supports this effective strategic path in light of the economic developments in the international arena. The movement of foreign investment has kept pace with the historical developments that Algeria experienced during the construction of its socialist economy through plans after independence, and to the great turn it took after the oil crisis towards a market economy and the accompanying structural reforms in order to know the conditions that foreign investment has reached in light of the reforms, which is What we will cover in this research. Algeria also possesses energy potential in this field, which qualifies it to build a diversified and strong economy. However, foreign investment in these energies in Algeria encounters many obstacles, such as high costs, lack of seriousness in investing in this sector..., consumption of traditional energy Currently, it is considered the best path for economic growth in the short to medium term in Algeria, because renewable energies investments require government support, in addition to the difficulty of replacing the structures and structures of the exploitation of traditional energies with renewable energy technologies currently due to the high costs and young technology in the market, in addition to the characteristics of Algeria's energy mix, which depends on Fossil fuels, which cannot currently be replaced by renewable energies applications without intervention by the government sector in the form of spending on research and development and encouraging the exploitation of renewable energies applications locally, which has led to a negative impact on growth rates. Our study concluded the following most important results: - That foreign direct investment does not cause the use of renewable energies at a significant level of 5%. - The use of renewable energies does not cause foreign direct investment at the level of morale of 5%. - Environmental pollution does not cause the use of renewable energies at a significant level of 5%. - The use of renewable energies does not cause environmental pollution at the level of significance 5%. - Environmental pollution does not cause foreign direct investment at the 5% morale level. - That foreign direct investment causes environmental pollution at the level of significance 5%."
ماستر تجارة
Keywords: الاستثمار الأجنبي المباشر - الطاقات المتجددة - الامكانات الطاقوية; Foreign direct investment - renewable energies - energy potential